Inspecting the corrosion state of underground reinforced concrete structures - Patrick Pfändler; Lukas Bircher; Ueli Angst (Journal of Infrastructure Preservation and Resilience, 2022)
Abstract Unnoticed corrosion in underground reinforced concrete structural members – such as foundations, retaining walls, or piles – may severely threaten the integrity of structures. However, condition assessment of the ground-buried structural parts is challenging, because the areas of interest are hardly accessible for visual inspection or non-destructive testing. An example of particular practical relevance is reinforcement corrosion at the back-side of the lower end of cantilever retaining walls, near the construction joint between stem and heel of the base slab. The collapse of a cantilever retaining wall in Austria was a tragic reminder of the dangers of unnoticed corrosion. The drawback of current inspection methods is that they are laborious and costly, but still, only a tiny fraction of the structure can be inspected. Considering that the degree of corrosion can vary significantly along a structure, such local information includes a risk that corrosion elsewhere remains undetected. A novel inspection system is proposed here, combining the well-proven half-cell potential measurement technique with steered horizontal underground drilling technologies. With this approach, a tailor-made probe is brought in proximity to the concrete surface in the soil and electrochemical measurements are performed to characterize the corrosion condition. The main advantage is that virtually the entire length of the structure can be inspected, thus overcoming the limitations of highly local inspection. Moreover, the proposed technique includes a method to constantly monitor the functionality of the potential measuring probe, based on electrical resistance measurements. The feasibility of the approach was confirmed in laboratory experiments on a mortar block in soil. These findings were confirmed in a field experiment. The results suggest that local corroding zones of practice-relevant size can be detected for a distance between the reference electrode and the steel surface of at least 25 cm. On the basis of this work, underground corrosion inspection of cantilever retaining walls is considered feasible, and the development of similar technologies as the one proposed here may in the future considerably enhance condition assessment of structures buried in the ground.